2021
DOI: 10.1038/s41438-021-00687-9
|View full text |Cite
|
Sign up to set email alerts
|

A 2.09 Mb fragment translocation on chromosome 6 causes abnormalities during meiosis and leads to less seed watermelon

Abstract: Seedlessness is a valuable agronomic trait in watermelon (Citrullus lanatus) breeding. Conventional less seed watermelons are mainly triploid, which has many disadvantages due to unbalanced genome content. Less seed watermelon can be achieved at the diploid level when certain reproductive genes are mutated or by chromosome translocation, which leads to defects during meiosis. However, the formation mechanism of diploid less seed watermelons remains largely unknown. Here, we identified a spontaneous mutant line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 61 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…That was to say, the abnormal meiosis of H30-6 was not caused by polyploidization. A recent report showed that a 2.09 Mb chromosome fragment translocation causes abnormalities during meiosis and leads to pollen semisterility and fewer seeds in watermelon (Tian et al, 2021 ). Additionally, the fragment translocation results in one quadrivalent ring of four chromosomes at prometaphase I during meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…That was to say, the abnormal meiosis of H30-6 was not caused by polyploidization. A recent report showed that a 2.09 Mb chromosome fragment translocation causes abnormalities during meiosis and leads to pollen semisterility and fewer seeds in watermelon (Tian et al, 2021 ). Additionally, the fragment translocation results in one quadrivalent ring of four chromosomes at prometaphase I during meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Potato ( Solanum chacoense ) ScRALF3 participates in both male and female gametophyte development. Scralf3 mutants produced pollen grains with reduced viability and fewer seeds, primarily due to abnormal nuclear distribution and asynchronous nuclear divisions in the embryo sac [ 120 , 121 ].…”
Section: Female Sterilitymentioning
confidence: 99%
“…The GWAS results of fruit firmness in Pyrus revealed that an identical-by-descent segment harboring a 12 bp insertion in TIC55 determined fruit softening [ 16 ]. After the release of watermelon genome [ 17 , 18 ], functional genomic studies for important quality and storability relevant traits are also facilitated [ 19 22 ]. ClERF4 gene influencing fruit rind hardness and cracking was fine-mapped through BSA-seq in watermelon [ 20 ].…”
Section: Introductionmentioning
confidence: 99%